GROWTH OF NYPA PALM WORMS (Namalycastis rhodochorde) JUVENILES FED ON NYPA PALM FRONDS FERMENTED BY CELLULOLYTIC BACTERIA NrLtC4 AND NrLtG2 - Hosiana Patricia Sheren; Ari Hepi Yanti; Tri Rima Setyawati; Rikhsan Kurniatuhadi (BRIN Publishing (Penerbit BRIN), 2025)
Nypa palm worms (Namalycastis rhodochorde: Polychaetes) play important ecological roles as detritivores of organic matter in mangrove ecosystems, bioindicators of water pollution, and sediment stabilizers in estuarine environments. N. rhodochorde also shows potential for use in fermented feed-based aquaculture due to its high nutritional value as a natural food source for aquatic organisms. Cellulolytic lactic acid bacteria isolated from the coelomic fluid and gastrointestinal tract of N. rhodochorde, identified as isolates NrLtC4 and NrLtG2, have potential as starter cultures for fermenting niypa palm fronds, which are used as feed in nypa palm worm cultivation. This study aimed to evaluate the growth of juvenile N. rhodochorde fed nypa palm fronds fermented by the cellulolytic bacteria NrLtC4 and NrLtG2. Juveniles were maintained under consistent stocking density, container size, and water volume, with three treatments arranged in a completely randomized design: unfermented nypa palm fronds (control), nypa palm fronds fermented with isolate NrLtC4, and nypa palm fronds fermented with isolate NrLtG2. The results demonstrated that fermented feed significantly influenced both the number of body segments [p = 0.00021 and 0.0028 (p < 0.05)] and body length [p = 0.0020 and 0.0035 (p < 0.05)] of the juveniles. Juveniles fed nypa palm fronds fermented with strain NrLtC4 showed increases of 29.6% in segment number and 58.5% in body length, while those fed fronds fermented with strain NrLtG2 exhibited increases of 36.6% and 63.9%, respectively. The highest juvenile survival rate was observed in the NrLtC4 fermented feed group at 72%, followed by 69.33% in the NrLtG2 group. These findings suggest that bacterial isolates NrLtC4 and NrLtG2 have promising potential as a consortium feed to enhance the growth of nypa palm worms in aquaculture.